Evaluation of lipid liquid crystalline phase particles as drug delivery vectors - Xerri, Rachael (2021)
Lipids, of the glyceride sub-species, are amphiphilic molecules that will self-assemble in aqueous conditions. Based on the lipid’s critical packing parameter (CPP), i.e., the ratio between the lipid tail length, tail volume and the lipid head area, the lipids may self-assemble into different liquid crystalline phases, such as lamellar or cubic phases. Such phases may then be stabilised into discrete nanoparticles in an aqueous suspension through the utilisation of a polymer, namely here poloxamers. These stabilised liquid crystalline particles have many of the advantages of liposomes (one of the most used lipid nanoparticle formulations) such as biocompatibility and the ability to encapsulate both hydrophobic and hydrophilic moieties. Liquid crystalline phases additionally offer an improved stability of the formulation’s physicochemical properties and API stability during storage and in vivo compared to other lipid nanoparticle formulations; increasing the shelf-life of formulations and offering a wide variety of formulation administration strategies i.e. intravenous, intramuscular, oral. The primary types of liquid crystalline phases found within the literature, particularly for pharmaceutical applications, are cubosomes and hexasomes, formed from cubic phases and hexagonal phases respectively.